“Other Materials” — Traitorous Love and Decolonizing the Canadian Guide to Uniform Legal Citation - Lussier, Danielle; Stechly, Steven (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2021)
The Canadian Guide to Uniform Legal Citation, colloquially known as the “McGill Guide,” is both a strong symbol of, and a prerequisite for, any form of engagement within Canadian legal academia. While studying law requires a deep understanding of the Guide, it does not inherently encourage interrogation of the pedagogical structures the Guide upholds. In this sense, critical engagement with the politics of citation is often overlooked in legal curricula.Examining their own attempts to centre Indigenous knowledge systems in legal research, the authors suggest that a critical failure in efforts towards decolonization of the legal academy resides in the exclusionary and Eurocentric nature of legal citation practices. They argue that citational politics become more problematized when scholars must “fit” Indigenous Knowledge into one of the pre-existing Western sources of law included in the Guide, a process that frequently results in Indigenous Knowledge being relegated to the unenviable bibliographic category of “other materials.”The authors argue that there is an opportunity to valourize long-subjugated Indigenous knowledge and amplify voices often silenced within the academy through the decolonization of legal citation methods. Situating the conversation of Indigenous citation politics and exploring the input of Indigenous librarians and scholars from a variety of academic fields, the authors survey a variety of citation manuals across disciplines and present the case for creating inclusive Indigenous legal citation practices. Beyond Indigenous oral knowledge citation, the authors specifically turn their minds to the citation of wampum and “extra-intellectual knowledge” including art, beadwork, and personal knowledge such as dreams, encouraging learners and researchers to engage in thoughtful citation practices and imagine decolonial legal futures grounded in a spirit of traitorous love.